2015
DOI: 10.1371/journal.pone.0121087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Glucose Administration on Rebound Growth Hormone Release in Normal and Obese Women: The Role of Adiposity, Insulin Sensitivity and Ghrelin

Abstract: ContextMetabolic substrates and nutritional status play a major role in growth hormone (GH) secretion. Uncovering the mechanisms involved in GH secretion following oral glucose (OG) administration in normal and obese patients is a pending issue.ObjectiveThe aim of this study was to investigate GH after OG in relation with adiposity, insulin secretion and action, and ghrelin secretion in obese and healthy women, to further elucidate the mechanism of GH secretion after OG and the altered GH secretion in obesity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 55 publications
0
18
0
1
Order By: Relevance
“…Another potential mechanism may be HbA1c [39], however in the present article we could not find a significant influence of the HbA1c value on the resistance to TH indices. There is an important relationship between the GH-IGF-1 axis and obesity [8][9][10]40], and circulating GH modulates the thyroid axis. Circulating GH levels increased serum FT3 and decreased serum FT4 in humans [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential mechanism may be HbA1c [39], however in the present article we could not find a significant influence of the HbA1c value on the resistance to TH indices. There is an important relationship between the GH-IGF-1 axis and obesity [8][9][10]40], and circulating GH modulates the thyroid axis. Circulating GH levels increased serum FT3 and decreased serum FT4 in humans [41].…”
Section: Discussionmentioning
confidence: 99%
“…Excess body fat is associated with endocrine alterations, including decreased GH secretion [8][9][10] and thyroid dysfunction [10,11]. Thyroid hormone levels have been reported to be normal, increased, and decreased in obese patients; this discrepancy probably reflects the fact that the patients were examined at different times and may differ in degree and type of obesity and metabolic complications [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Nass et al [ 37 ] found that endogenous acylated ghrelin increases the amplitude of GH pulses. Ghrelin secretion is decreased in obesity [ 38 ] and this decrease could be responsible, at least partially, for the alteration of GH secretion observed in obese individuals [ 10 ]. The IGF-1 feedback mechanism is preserved in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Excess body fat is associated with endocrine alterations, including thyroid dysfunction, central resistance to thyroid hormones [ 7 , 8 ] and decreased growth hormone (GH) secretion [ 9 , 10 , 11 ]. The altered GH secretion of obesity can be reversed by body weight normalization [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a multivariate analysis, ghrelin was the only predictor for fasting and peak GH levels following oral glucose load in women [16] (Fig. 1).…”
Section: Gh Response To Oral Glucose and To Chronic Hyperglycemiamentioning
confidence: 99%